Simulation of lamb wave interactions with defects in a thin plate - Nurazima, Ismail; Z. M., Hafizi; Che Ku Eddy Nizwan, Che Ku Husin; S., Ali (IOP Publishing, 2019)
The understanding of Lamb wave propagation and its interaction with defects are crucial part of SHM technology. Being of high relevance due to the costs of experimental equipment, the dynamic finite element analysis is performed in this study. FEA analysis was implemented to simulate propagation of Lamb waves in healthy and defective aluminium plate. The wavefield visualisation shows a high degree of difference between these two plates, which shows the interaction with defects. This study is useful for a good understanding of the Lamb wave interaction with defect before applying this method for a real application.